COMPLIMENT STRATEGIES PRODUCED BY EFL LEARNERS OF ENGLISH STUDY PROGRAM IN RIAU, INDONESIA - Ariani, Lili; Purwanti, Indah Tri; Eliwarti (International Journal of Educational Best Practices, 2021)
This research was aimed at analysing students' strategies in giving compliments. This was descriptive qualitative research using a qualitative approach accompanied by descriptive statistics. This research involved 39 EFL students as the participants in the academic year 2019/2020 selected using cluster random sampling technique. The instrument used to collect the data was a DCT (Discourse Completion Test) containing several situations where the students were expected to give their compliments. The result showed that the students used many kinds of strategies in giving compliments. The explicit strategy was the most used by the students. Furthermore, the single explicit strategy appeared the most within overall strategies that appeared in the DCT. This implied that the students prefer to give a direct and simple compliment. One strategy in giving compliments appeared out of the classification which is congratulation attached to an unbound semantic formula.